Tests and indicators for improving the pedagogical control of the legs force of long and middle distance, as well as sport walk 12-15 school categories athletes - Ernesto Santana-García; Osmani Otaño Salgado; Rolando Acosta-Castro (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2014)
The control of the yield inside the process of sport training is one of the instruments that guarantee that it is made on the base of solid arguments as for the correspondence among the loads or preparation stimuli that must receive the sportsman and its condition to assimilate it. Due to the deficiencies, detected during a preliminary diagnosis based on the content analysis, measurement and mathematical statistical methods that corroborate the necessity to perfect elements of the sportsmen preparation management, a study begins with the in o rde r to give solution to the scientific problem: How to improve the pedagogic control of the legs force on Long and Middle distance, as well as Sport Walk athletes at 12 - 15 yeas school categories from "Ormani Arenado" Initial Sport School of Pinar del Río? It has the objective to select tests and indicators that improve this pedagogic control. There were used different methods and investigation instruments such as, analysis and synthesis, the measurement, as well as the descriptive and inferential statistic, which allowed the selection of the test of the ten jumps to include it in the protocol of evaluation of the physical performance set for the school categories, with procedures that brings forth four indicators on the sportsman's state. Its feasibility is being evaluating at present in an extended study certified by the provincial commission of Athletics. The contributions of this research, favor to the results of the investigative project "The evaluation and planning of the training in Long and Middle distance, as well as Sport Walk athletes in Pinar del Río", answering, at the same time, to the fourth technological demand of the Athletics in this western county of Cuba.